Importance of epiphytic populations in the epidemiology of bacterial diseases (Revista de Ciências Agroveterinárias, 2009)
Host and non-host plants, including weed and forage species, take part in the life cycle of phytopathogenic bacteria, serving as repository of inoculum to infect agronomic crops. This paper addresses characteristics of the epiphytic population regarding to the epidemiology of phytopathogenic bacteria. It also characterizes the importance of weed control and the use of resistant cultivars to prevent bacterial diseases. The epiphytic populations are directly related to the occurrence of epidemics and their control is an important tool in the integrated management of bacterial diseases.
Keywords: bacteria; surviving; epiphytic.